Nano-Silica and its Role on Performance of Cement Concrete-A Review of Experimental Investigation. Issue 1 (December 2020) - Paktiawal, A; Alam, M
Abstract: The researchers are generally focusing on the basic technology of cementitious materials at the nano level. In addition, the researchers are mainly aimed at enhancing the durability and strength of concrete and have found rapidly developing the mechanical and microstructural properties of cementitious materials with the introduction of nano-silica. The present paper reviewed and summarized the experimental research works carried out on the use of nano-silica in cement concrete mix as an additive or replacement of cement and its effects on rheology of the fresh concrete, and properties of hardened concrete such as strength, and durability. Thus, nano-silica is a promising material which can be used to improve the properties of the cement concrete.